Notch signaling in the vasculature: angiogenesis and angiocrine functions - Safatul Hasan, Sana (Cold Spring Harbor perspectives in medicine, 2023)
Formation of a functional blood vessel network is a complex process tightly controlled by pro- and antiangiogenic signals released within the local microenvironment or delivered through the bloodstream. Endothelial cells precisely integrate such temporal and spatial changes in extracellular signals and generate an orchestrated response by modulating signaling transduction, gene expression, and metabolism. A key regulator in vessel formation is Notch signaling, which controls endothelial cell specification, proliferation, migration, adhesion, and arteriovenous differentiation. This review summarizes the molecular biology of endothelial Notch signaling and how it controls angiogenesis and maintenance of the established, quiescent vasculature. In addition, recent progress in the understanding of Notch signaling in endothelial cells for controlling organ homeostasis by transcriptional regulation of angiocrine factors and its relevance to disease will be discussed.
Gesehen am 28.03.2023